Cover Research Handbook on International Law and Environmental Peacebuilding Research Handbook on International Law and Environmental Peacebuilding - Dam-de Jong, Daniëlla; Sjöstedt, Britta (Edward Elgar Publishing, 2023)
This incisive Research Handbook addresses the growing recognition within the international law community that natural resource governance and environmental protection are crucial aspects of peace processes, both as a security imperative and as an opportunity for peacebuilding. Examining the impact of international normative and institutional frameworks on environmental peacebuilding, this Research Handbook features contributions from distinguished experts and global case studies on integrated legal approaches to the governance of natural resources.